PERAN PEMERINTAH DAN MASYARAKAT DALAM PENGEMBANGAN PUAR LOLO SEBAGAI DAYA TARIK EKOWISATA DI MANGGARAI BARAT NUSA TENGGARA TIMUR - Wulandari, Anastasia Ketrin; Adikampana, I Made (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Puar Lolo is a protected area. Puar Lolo is located in the Mbeliling landscape, on the Trans Flores road in Golo Damu Village, Mbeliling District, West Manggarai Regency, Flores, East Nusa Tenggara. It is a beautiful place to observe the Flores hawk. Puar Lolo is an ecotourism-based protected area tour whose potential has not received special attention from the community and related institutions. Based on the preminary studies Puar Lolo is a Mbeliling protected area, so far it has not been optimized because it is still focused on developing other ecotourism. The purpose of this research is to identify the potential of Puar Lolo as well as the role of the government and local communities in developing the ecotourism potential of Puar Lolo. With this type of research used is descriptive qualitative with data collection carried out by conducting observations, in-depth interviews, documentation and literature studies. The results of this study show that Puar Lolo has the tourism potential of the highest collection of bird species among conservation areas in Flores, beautiful natural scenery, as well as the potential for handicraft businesses, such as basket crafts (roto), and mats (mats).